Optimization of PTH/PTHrP Hybrid Peptides to Derive a Long‐Acting PTH Analog (LA‐PTH) - Noda, Hiroshi (JBMR Plus, 2020)
Prolonged signaling at the parathyroid hormone receptor 1 (PTHR1) correlates with the capacity of a ligand to bind to a G protein‐independent receptor conformation (R(0)). As long‐acting PTH (LA‐PTH) ligands hold interest as potential treatments for hypoparathyroidism (HP), we explored the structural basis in the ligand for stable R(0) binding and prolonged cAMP signaling. A series of PTH/PTHrP hybrid analogs were synthesized and tested for actions in vitro and in vivo. Of the series, [Ala(1,3,12),Gln(10),Arg(11),Trp(14)]‐PTH(1‐14)/PTHrP(15–36) (M‐PTH/PTHrP) bound with high affinity to R(0), induced prolonged cAMP responses in UMR106 rat osteoblast‐derived cells, and induced the most prolonged increases in serum calcium (sCa) in normal rats. Daily s.c. injection of M‐PTH/PTHrP into thyroparathyroidectomized (TPTX) rats, a model of HP, normalized sCa without raising urine Ca. In contrast, oral alfacalcidol, a widely used treatment for HP, normalized sCa, but induced frank hypercalciuria. M‐PTH/PTHrP exhibited low solubility in aqueous solutions of neutral pH; however, replacement of Leu18, Phe22, and His26 with the less hydrophobic residues, Ala, Ala, and Lys, at those respective positions markedly improved solubility while maintaining bioactivity. Indeed, we recently showed that the resultant analog [Ala(18,22),Lys(26)]‐M‐PTH/PTHrP or LA‐PTH, effectively normalizes sCa in TPTX rats and mediates prolonged actions in monkeys. These studies provide useful information for optimizing PTH and PTHrP ligand analogs for therapeutic development. © 2020 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.